Enhanced Ammonium Adsorption from Aqueous Solutions Using Ethylenediaminetetraacetic Acid (EDTA) Modified Lampung (Indonesia) Natural Zeolite: Isotherm, Kinetic, and Thermodynamic Studies - Abelta, Gita Aldira; Al Qadri, Latif; Febrina, Melany; Rajak, Abdul; Maulana, Sena; Asagabaldan, Meezan Ardhanu; Taher, Tarmizi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
The environmental concern related to excessive ammonium in water bodies necessitates efficient and cost-effective removal techniques. This study investigated the modification of natural zeolite collected from the Tanggamus district of Lampung Province, Indonesia, with ethylenediaminetetraacetic acid (EDTA) to enhance its performance for ammonium adsorption from aqueous solution. The modified and natural zeolites were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), N2 adsorption-desorption isotherm, and scanning electron microscopy (SEM). Results indicated that the modification did not cause significant structural changes but increased the mesoporosity of the zeolites, which was beneficial for ammonium adsorption. The adsorption studies revealed that the EDTA modified zeolites consistently outperformed the natural zeolite and that the adsorption process was exothermic in nature. The Langmuir and Freundlich isotherm models fit the adsorption data well, indicating that the adsorption process occurs on both homogenous and heterogeneous surfaces. Thermodynamic studies confirmed that the adsorption process was exothermic and that the EDTA modification increased the spontaneity of the ammonium adsorption process. Overall, this study highlights the potential of EDTA-modified zeolites as an effective material for ammonium removal from aqueous solutions.